Village Public Expenditure Management in Indonesia : Towards Better Budgeting and Spending - World Bank (World Bank, Washington, DC, 2021)
This report represents the largest assessment of village spending since the enactment of the Village Law. The findings presented here are based on a public expenditure analysis of financial data from 45,625 rural villages across 248 districts and 33 provinces. This represents over 58 percent of all villages, although coverage of villages by province varies between 5 percent in Papua Barat to 100 percent in Bali. The objective of this report is to provide an initial assessment of Indonesia's village spending and budget credibility, which will in turn strengthen the ability of the Government of Indonesia and village administrations to solve the pressing problems facing rural communities. The report is structured into four parts: analysis of village reporting, expenditures, revenues, and performance.